Anisogrid cylindrical CFRP shell structures under static axial compression – experiments and finite element modeling - Vasanthanathan, A.; Nagaraj, P.; Thilak, J. Anish Jafrin (Journal of Structural Engineering, 2025)
Carbon Fibre Reinforced Plastic (CFRP) lattice shell structures are preferred in spacecraft applications such as rocket interstages, payload adapters in launch vehicle and aircraft fuselage components. There is a necessity to improve the structural efficiency of these structures to withstand various loads, especially axial compression and impact. This paper presents the unidirectional material characterization of CFRP, finite element (FE) modeling and experimentation of CFRP composite cylindrical shells viz., unstiffened and anisogrid under static loading conditions. Finite element analysis (FEA) of unstiffened and anisogrid composite shell structures have been conducted by using ANSYS® Workbench for axial static compression. The material model and material properties of the entire FEA is based upon the mechanical characterization. Static axial compression tests have been carried out in UTM and the results are compared with FEA results. Based on FE A and experimental results, it is inferred that the CFRP anisogrid shell structures possess maximum load carrying capacity than unstiffened shell structures.